TOPICAL IMMUNOCORRECTION IN PROPHYLAXIS AND TREATMENT OF FREQUENTLY AND LONG AILING CHILDREN - Ye. A. Vishneva; A. A. Alekseyeva; Yu. G. Levina; R. M. Torshkhoyeva ("Paediatrician" Publishers LLC, 2011)
Treatment and prophylaxis of acute respiratory infections remain serious social and economical problem. Modern medicine estimates immunomodulators as one of promising methods of treatment and preventing of acute respiratory infections (ARI) especially in frequently and long ailing children. Prophylactic administration of immunomodulators allows decreasing the risk of recurrent ARI, and treatment with these drugs in acute phase shortens terms of a disease and compensates immunosuppression.